2021
DOI: 10.21203/rs.3.rs-690673/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Interfacial crystallization and supramolecular self-assembly of spider silk inspired protein at the water-air interface

Abstract: Macromolecular assembly into complex morphologies and architectural shapes is an area of fundamental research and technological innovation. In this work, we investigate the self-assembly process of recombinantly produced protein inspired by spider silk (spidroin). To elucidate the first steps of the assembly process we looked into highly concentrated and viscous pendant droplets of this protein in air. We show how the protein self-assembles and crystallizes at the water-air interface into a relatively thick an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…Previously, Mohammadi et al showed that similar silk-like proteins can self-assemble at the water−air interface of a droplet in a manner that is both timeand RH-dependent. 47 Furthermore, they noticed a significant difference in the β-sheet content between 40 and 80% RH, 47 an observation consistent with our findings that the most dramatic change happens in the range of 45−65% RH. The effect of the protein concentration on CA indicates that a moderate amount of protein is better provided that the film contains enough protein for full surface coverage.…”
Section: Resultssupporting
confidence: 88%
“…Previously, Mohammadi et al showed that similar silk-like proteins can self-assemble at the water−air interface of a droplet in a manner that is both timeand RH-dependent. 47 Furthermore, they noticed a significant difference in the β-sheet content between 40 and 80% RH, 47 an observation consistent with our findings that the most dramatic change happens in the range of 45−65% RH. The effect of the protein concentration on CA indicates that a moderate amount of protein is better provided that the film contains enough protein for full surface coverage.…”
Section: Resultssupporting
confidence: 88%
“…Measurements were performed with an energy exposure of 15 keV (0.82656 Å) using a silicon 111 monochromator and a beam size of 100 μm. Data were recorded using an Eiger X 9M detector with a pixel size of 75 μm × 75 μm, as reported previously ( 56 , 57 ). The measurements were carried out under ambient conditions at 50% RH.…”
Section: Methodsmentioning
confidence: 99%
“…The process was continued until the stable foam was formed by the self-assembly of 4RepCT proteins at the air−water interface. 519 The other promising applications of recombinant silk are hydrogels with 95−97% w/w water content and a high swelling ratio. 520 Schacht et al 521 demonstrated the use of ADF4 hydrogel as cytocompatible bioinks in additive manufacturing of hierarchical tissue-like structures by incorporating living cells.…”
Section: Silk-and Silk-based Materialsmentioning
confidence: 99%